Integration of inquiry-based experiences department-wide: an example from biology curriculum: Radically embedding a high-impact practice for equity and access. - Singhal, Sonal; Kram, Karin; Valliere, Justin; Wang, Fang; Heckel, Brynn; Leigh, Samantha; Theiss, Kathryn; McCord, Charlene; Soroosh, Artin; Taylor, Thomas; et al. (Experiential Learning and Teaching in Higher Education, 2024)
Inquiry-based course experiences provide a scalable and equitable way to engage students in research. In this study, we describe how we introduced inquiry-based experiences to ten lower-division and upper-division courses across the biology curriculum at a regionally comprehensive public university serving the diverse population in a major metropolitan area. Student survey data suggest this redesign effectively developed students’ scientific skills and nurtured their sense of belonging. This project illustrates how inquiry-based experiences can be implemented sustainably across institutional context.